2013
DOI: 10.1002/gps.4056
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce the number of falls among older adults with/without cognitive impairment: an exploratory meta‐analysis

Abstract: Single exercise interventions can significantly reduce numbers of falls among older adults with and without cognitive impairment in institutional or non-institutional settings. Vitamin D and calcium supplementation, home visits, and environment modification can reduce the risk of falls among older adults in non-institutional settings. Exercise-related multiple interventions and multifactorial interventions may only be effective for preventing falls in older adults with cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 30 publications
3
53
0
1
Order By: Relevance
“…To our knowledge, this is the first study to demonstrate this association over a long follow-up period. A strong body of evidence illustrates the value of exercise in fall prevention in elderly adults [6][7][8][9][10]. A recent review of meta-analyses of RCT of fall prevention interventions in community-dwelling older adults highlights the consistent evidence that exercise reduces falls [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study to demonstrate this association over a long follow-up period. A strong body of evidence illustrates the value of exercise in fall prevention in elderly adults [6][7][8][9][10]. A recent review of meta-analyses of RCT of fall prevention interventions in community-dwelling older adults highlights the consistent evidence that exercise reduces falls [6].…”
Section: Discussionmentioning
confidence: 99%
“…A strong body of evidence, including randomized controlled trials (RCT), has demonstrated the value of exercise in fall prevention in elderly adults [6][7][8][9][10]. However, the nature of these studies limit the follow-up period and longterm benefits, if any, are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The other six reviews included mixed populations of adults with and without cognitive impairment (Oliver, Connelly et al 2007, Jensen and Padilla 2011, Cameron, Gillespie et al 2012, Winter, Watt et al 2013, Guo, Tsai et al 2014. Persons with dementia.…”
Section: Figure 1: Flowchart Illustrating Reviews Identifiedmentioning
confidence: 99%
“…A number of reviews have investigated falls interventions in various cognitively impaired populations (Shaw 2007, Winter, Watt et al 2013, Guo, Tsai et al 2014. Meta-analysis of falls prevention programmes in adults with a cognitive impairment has previously been undertaken (Guo, Tsai et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation